EXPLORING VILLAGE ECONOMIC POTENTIAL FOR THE DEVELOPMENT OF VILLAGE-OWNED ENTERPRISE (BUMDES): CASE STUDY BUMDES AMANAH WONOSARI, GUNUNGKIDUL - Rohmah, Siti; Purbaningrum, Catarina Wahyu Dyah; Rochmadi, Imsak; Afriyanti (Universitas Tidar, 2024)
The village is deliberated as the smallest government organization that has the closest association with the community and various potentials as an economy driver towards sustainable development. The economic capability that exists in Gunungkidul Regency refers to economic potential that can be developed to become a source of livelihood for the village. Village-Owned Enterprise or BUMDes is a business entity owned by the village, which was initiated as an effort to improve the welfare of the village’s people. BUMDes AMANAH was assigned in carrying out business activities, which are waste management, goods and services trading, and tourism. From the economic potential analysis of villages in Piyaman District, Piyaman, Wonosari, Gunungkidul, sectors that are covered are agriculture, agro-industry, agribusiness, crafts, natural beauty and educational tourism. This study employs qualitative research, which aims to describe and explain the natural data obtained thatput the researcher as the key instrument. Data collection with purposive sample and snowball resulting in an emphasis on generalization implication, and data quotations from facts revealed in the field, to be later presented in reports. Meanwhile, the existing business units require optimization efforts in various way to be sustainably implemented with strategies set based on internal and external constraints. Service optimization on existing business units require new breakthroughs in increasing revenue. Efforts to increase the capacity of Human Resources in managing BUMDes are also required. The role of the village government and full support for the progress of BUMDes are counted, by providing policies in business unit development and facilitation as well as reinforcing collaboration with Pentahelix synergy.